Formulation of new sourdough bread prototypes fortified with non-compliant chickpea and pea residues - Cutroneo, Sara; Petrusan, Janos-Istvan; Stolzenberger, Reiner; Zurlini, Chiara; Tedeschi, Tullia (Frontiers in Nutrition, 2024)
Nowadays, the promotion of a circular economy is fundamental to reduce food losses and waste. In this context, the possibility of using food supply chains non-compliant residues emerges. Much interest has been directed towards legume residues in general and, in particular, to the possibility of combining different plant-matrices to improve nutritional profile, providing high-quality products.Five different formulations of breadswith a combination of seeds and cerealswere fortified with chickpea-and pea-protein concentrates. Samples were analysed and compared with their relative control recipe to determine differences in composition, actual protein quality and integrity, and protein digestibility (performed with INFOGEST method).Samples showed a clear improvement in the nutritional profile with higher values of proteinsfrom averagely 12.9 17.7 (control breads) to 29.6 % to 24.7 g/100 g of dry matter (fortified breads) (17.7 to 24.7 g/100 g of dry matter respectively)and an improvement in amino acidic profile, with a better balancing of essential amino acids (lysine and sulphur amino acids contents), without affecting protein integrity. Regarding in vitro gastro-intestinal digestibility performed with INFOGEST method, sample C (19% chickpea proteins) showed the best results, having a comparable protein digestibility to its control bread -48.8 ± 1.1% vs 51.7 ± 2.3% respectively.Results showed how the fortification with chickpea and/or pea protein concentrate improved bread's nutritional profile. These prototypes seem to be a valid strategy to also increase the introduction of high biological value proteins. Furthermore, the not-expected lower digestibility suggested the possible presence of residual anti-nutritional factors in the protein concentrates interfering with protein digestibility. Therefore, it seems of fundamental importance to further investigate these aspects.